Cong nghiep hoa nong nghiep va phat trien nong thon Agricultural industrialization and rural development - Ngo, Xuan Binh; Xiao, Xinhuang (Nha xuat ban Khoa hoc t nhien va cong nghe, 2008)
Papers on analysis and assessments of achievement, impacts, challenges of industrialization and international integration to agricultures in Taiwan and Vietnam.